The Influence of ISO 31000-Based Risk Management in Mitigating Budget Fraud Risk in the Public Sector During Crisis: A Systematic Literature Review - Rafi Fadhlurrhman; Rela Sari (BUGIS : Journal of Business, Technology, & Social Science, 2026)
The world is currently in an era of systemic uncertainty, where crises demand rapid government responses, yet often create control dilemmas that increase the risk of budget fraud. This study aims to analyze the influence of ISO 31000-based risk management in mitigating the risk of budget fraud in the public sector during times of crisis through a Systematic Literature Review (SLR) approach. By following the PRISMA protocol, a total of 25 selected Scopus-indexed articles (spanning 2019–2026) were analyzed to synthesize the most effective mitigation patterns. The results indicate that the systematic implementation of ISO 31000, driven by legitimacy motivations in accordance with Institutional Theory, serves as a crucial instrument in strengthening organizational defenses against fraudulent practices. A key finding reveals that the integration of digital technologies such as Artificial Intelligence (AI) and real-time monitoring acts as an important catalyst in enhancing the ISO 31000 framework for detecting budget anomalies during emergencies. This study concludes that the success of fraud mitigation depends not only on technical compliance but also on the development of an adaptive integrity culture to maintain fiscal resilience and public trust.